Aberrant functional connectivity density in patients with treatment-refractory obsessive-compulsive disorder: a pilot study. Issue 6 (June 2019) - Shan, Pei Wei; Liu, Wei; Liu, Caixing; Han, Yunyi; Wang, Lina; Chen, Qinggang; Tian, Hongjun; Sun, Xiuhai; Luan, Shuxin; Lin, Xiaodong; Jiang, Deguo; Zhuo, Chuanjun
Objective: Functional connectivity (FC) is altered in patients with obsessive-compulsive disorder (OCD). Most previous studies have focused on the strength of FC in patients with OCD; few have examined the number of functional connections in these patients. The number of functional connections is an important index for assessing aberrant FC. In the present study, we used FC density (FCD) mapping to explore alterations in the number of functional connections in patients with treatment-refractory OCD (TROCD) using the FCD index. Methods: Twenty patients with TROCD and 20 patients with OCD in clinical remission were enrolled in the study. Global FCD (gFCD) was adopted to compare the differences between the two groups of patients. Results: The gFCD in the left middle temporal gyrus was lower in the patients with TROCD than in those with remitted OCD, suggesting that decreased information processing ability may play a significant role in TROCD. Conclusion: The left middle temporal gyrus is a key component of the emotional processing circuit and attentional processing circuit. Decreased information processing ability in this brain region may play a significant role in TROCD; however, further well-designed follow-up studies are needed to support this hypothesis.